2020
DOI: 10.1590/1678-4324-2020190348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Cellular Evaluation and Anatomical Organization of the External Region of Different Genetic Materials and Maturation Stages of Tomato Processing

Abstract: The effect of the anatomical structure of tomato skin may be significant for quality determination at the harvest point, but the definitions of cells that constitute the skin of fleshy fruits, such as tomato, are still unclear, providing contradictory descriptions. The aim of this study was to evaluate the epidermal tissue of different genetic materials of tomato processing (IT761, U2006, TC2736, CVR2909 and F3060) and maturation stage, in order to compare and choose genetic materials with morphological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is possible to confirm this with the correlation of split fruits with fruit weight and size and the inverse relationship with the color parameters (Figures 2 and 3), showing that as the fruits advance in maturity, there is a tendency of rupture occurrences. Such factor may also be associated with cuticle thickness, as according to Vieira et al (2020) when analyzing tomatoes at different stages of maturation, found that cuticle thickening increases during development and decreases in fully ripe fruits. This is due to the fact that cuticle deposition ceases before complete ripening of the fruits, so that ripe fruits have less cuticle per surface unit, meaning, thinner cuticle.…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to confirm this with the correlation of split fruits with fruit weight and size and the inverse relationship with the color parameters (Figures 2 and 3), showing that as the fruits advance in maturity, there is a tendency of rupture occurrences. Such factor may also be associated with cuticle thickness, as according to Vieira et al (2020) when analyzing tomatoes at different stages of maturation, found that cuticle thickening increases during development and decreases in fully ripe fruits. This is due to the fact that cuticle deposition ceases before complete ripening of the fruits, so that ripe fruits have less cuticle per surface unit, meaning, thinner cuticle.…”
Section: /8mentioning
confidence: 99%
“…The loss of water, either by the decrease of turgidity due to cracks or by the increase of respiratory activity, is one of the main problems of postharvest, resulting in the loss of luminosity, weight and shrinkage of the fruits (Figure 3), causing the useful life of pepper fruits to be reduced (Aloni et al, 1999;Finger & Pereira, 2016). Therefore, the thicker the cuticle is at the harvest stage, the longer will be the durability of this fruit (Vieira et al, 2020). Thus, it is important that the fruit harvest is performed at the optimal maturity stage to minimize water losses during storage and the marketing period (Lufu et al, 2020).…”
Section: /8mentioning
confidence: 99%